USING THE KAHOOT APPLICATION IN EVALUATING INFORMATICS ENGINEERING STUDENTS' LEARNING ENGLISH AT THE STATE POLYTECHNIC OF BENGKALIS - Wahana, Desi; Satria, Ari; Zahraa, Safra Apriani (Politeknik Negeri Bengkalis, 2024)
Abstract: Many educators started to utilize technology application activities in the classroom. Kahoot is known to be an interactive approach to conducting quizzes or tests. In this study, the author discusses using the Kahoot application in evaluating informatics engineering students learning English. A qualitative approach utilizing data by using tests and documentation by taking a sample of 15 students undergoing the Applied Bachelor in Informatics Engineering Program. The findings using Kahoot are effective as an assessment of learning English and students' scores got very good category (6 students) with 40% percent from all 15 students involved. Keywords: Kahoot, Application, English Learning